‘Long live Harry and Meghan!’: an analysis of polite and aggressive argumentation strategies from online forums on celebrity-related news - Simoes, Elsa (Redis: Revista de Estudos do Discurso, 2019)
The Royal Wedding of Prince Harry and Meghan Markle took place in Windsor, on 19 May, 2018. Prior to the event, the bride’s nationality, profession, marital status and ethnicity were already news fodder for tabloids and society magazines. The couple’s high visibility made them targets for supportive comments, as well as hate speech and verbal aggression. At the time of the wedding, an array of contradictory online comments could be found in newspapers, often with extreme opinions being voiced. A sample of comments found on The Daily Telegraph on the 19th May will be looked into, focusing on different aspects of the ceremony. To explore the functioning of argumentation within such a contemporary arena for public discussion, it is the purpose of this paper to elaborate on the ways of expressing lines of reasoning displayed in these online comments, with argumentation strategies for agreement or disagreement about previously expressed points of view, either general in tone, or appearing as a thread in response to a specific commentator. Specific arguments are often put forward, to persuade others; disagreement is often established by poking fun at others’ contributions, whereas humour can be effective for face-saving purposes or for deflecting aggressive ‘ad hominem’ comments.